Expression, purification, and characterization of a His6-tagged glycerokinase from Pichia farinosa for enzymatic cycling assays in mammalian cells - Janke, R.; Genzel, Yvonne; Freund, S.; Wolff, M. W.; Grammel, H.; Ruehmkorf, C.; Seidemann, J.; Reichl, Udo; Wahl, Sebastian Aljoscha (Journal of Biotechnology, 2010)
The GUT1 gene of the halotolerant yeast Pichia farinosa, encoding glycerokinase (EC 2.7.1.30), was expressed in Pichia pastoris. A purification factor of approximately 61-fold was achieved by a combination of nickel affinity and anion exchange chromatography. The specific activity of the final preparation was 201.6 units per mg protein with a yield of about 21%. A nearly homogeneous enzyme preparation was confirmed by SDS-polyacrylamide gels and mass spectrometry analysis. Glycerol stabilized the purified enzyme for long-term storage at -80°C. The pH and temperature optima were in the range of 6.5-7.0 and 45-50°C, respectively. ATP was the most effective phosphoryl group donor tested. Additionally, the enzyme phosphorylated glycerol also with ITP, UTP, GTP and CTP. The Km values of the enzyme for ATP and ITP were 0.428 and 0.845mM, respectively. The kinetic properties of the enzyme with respect to UTP, GTP, and CTP suggested that glycerokinase exhibited negative cooperativity as double reciprocal plots showed a biphasic response to increasing nucleoside triphosphate concentrations. The application as a coupling enzyme in the determination of pyruvate kinase activity in cell extracts of Madin-Darby canine kidney cells showed good reproducibility when compared with a commercially available preparation of bacterial glycerokinase. © 2010 Elsevier B.V.
CRIS-Team Scopus Importer:2022-01-11
Keywords: Glycerokinase; Ion exchange chromatography; Nickel affinity chromatography; Pichia farinosa; Protein expression; Protein purification